2007
DOI: 10.1007/s11845-007-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for ilioinguinal/iliohypogastric nerve block: a pilot study

Abstract: Ultrasound guidance for ilioinguinal and iliohypogastric nerve block in the inguinal region is both feasible and a promising technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
(20 reference statements)
1
17
0
1
Order By: Relevance
“…Iliohypogastric nerve entrapment manifests with pain and dysesthesia at the surgical site that radiates to the hypogastric area (38,39). Ilioinguinal nerve entrapment manifests with pain and dysesthesia at the surgical site that radiates to the inguinal area, labia majora, or scrotum (40)(41)(42). Occasionally, there may be tenderness medial to the anterior superior iliac spine.…”
Section: Mr Neurographic Findings In Individual Nerve Branches Iliohymentioning
confidence: 99%
See 1 more Smart Citation
“…Iliohypogastric nerve entrapment manifests with pain and dysesthesia at the surgical site that radiates to the hypogastric area (38,39). Ilioinguinal nerve entrapment manifests with pain and dysesthesia at the surgical site that radiates to the inguinal area, labia majora, or scrotum (40)(41)(42). Occasionally, there may be tenderness medial to the anterior superior iliac spine.…”
Section: Mr Neurographic Findings In Individual Nerve Branches Iliohymentioning
confidence: 99%
“…Occasionally, there may be tenderness medial to the anterior superior iliac spine. Electrodiagnostic testing is not reliable for diagnosing iliohypogastric or ilioinguinal neuropathy; positive nerve blocking with local anesthesia may be necessary to establish a diagnosis (40). It is noteworthy that a correctly performed negative nerve block is more specific for ilioinguinal nerve entrapment than a positive nerve block.…”
Section: Mr Neurographic Findings In Individual Nerve Branches Iliohymentioning
confidence: 99%
“…Although we did not found significant difference between two techniques, the other studies recommended using sonography for ilioinguinal nerve block. [16,17] Papadopoulos et al, [18] demonstrated that the outcome of ilioinguinal block was distinctive in different ages, but in our study two groups were matched in the view point of age.…”
Section: Resultsmentioning
confidence: 62%
“…In some patients, both nerves may not be visualized, and injectate can be administered to the plane between TA and IO muscles. 87 The technique for blocking the genital branch of the GF nerve under ultrasound guidance has only been described in a single review article. 4 A linear probe of high frequency (6Y13 MHz) is used.…”
Section: Technique For Ultrasound-guided Injectionmentioning
confidence: 99%